SERVICE QUALITY AND HOTEL CUSTOMER SATISFACTION: A CASE STUDY FROM DURRES, ALBANIA - ROBERT KOSOVA; VALENTINA SINAJ (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2020)
The purpose of using the study is to explore the connection and relationship between service and customer satisfaction in the Industry of tourism, in Albania. In recent years, in particular, the evaluation of service quality and customer satisfaction is considered an important objective of the tourism industry, hotels, restaurants, and other tourism services. The relationship between hotel service and the level of customer satisfaction has been studied, especially recently in research, conferences, articles. Hotel managers, restaurants, need to focus not only on good and quality service to new customers but also on retaining existing customers. In addition, they can only do so by knowing, respecting, and meeting their expectation of service. Therefore, measuring and evaluating customer service satisfaction to answer questions; Are the clients satisfied with the hotel service, will they come back again, will they recommend the hotel to their friends and colleagues, will they speak well on social networks and tourist service forums, etc.? Forgetting the quality of service in hotel tourism services can lead to negative evaluations of these hotels, limiting the possibility of repeating customers and the decline numbers of new customers. In this study, we have made a quantitative and qualitative analysis of some hotels in the coastal city of Durres, with more than 20-year experience in the tourism industry, along with hundreds of other hotels not only in Durres but also in other coastal cities in Albania. For this purpose, the Servqual evaluation method is used, which uses five basic factors in evaluating customer satisfaction